Effectiveness of fouling mechanism for bacterial immobilization in polyvinylidene fluoride membranes for biohydrogen fermentation - Engliman, Nurul Sakinah; Md. Jahim, Jamaliah; Abdul, Peer Mohamed; Tang, Pei Ling (Elsevier, 2020)
Bacterial immobilization was successfully develop using the fouling mechanism on the modified polyvinylidene fluoride membrane surface. The immobilization of bacteria via this method was accomplished through adsorption and entrapment of the bacteria in/on the membrane surface through fouling mechanism. Previously, the membrane was modified by polymerization method to impregnate the iron nanoparticles on the membrane surface in order to increase the surface roughness. The presence of both organic substances and bacterial cells leads to ‘combine fouling’ as the organic substances covalently bind the bacterial cells to the membrane by cross-linking, thus promote the efficiency of bacterial immobilization. The immobilized membrane was used for biohydrogen production via anaerobic fermentation using glucose-based media and it was found that it was capable of augmenting the yield of hydrogen production by 22% relative to the suspended system. This is attributed to the presence of iron on the membrane surfaces which come from the polymerization process that supplies the iron necessary for activating the hydrogenase enzyme in the bacteria, and hence, increase the production of biohydrogen. The metabolites analysis has indicated that the hydrogen production followed the acetic acid pathway.